FORMATION OF A HEALTHY LIFESTYLE IN STUDENT YOUTH - Jurayev Vohidjon Muhammedovich,; Kimsanov Oybek, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the student gives information about the creation of educational courses for young people to consciously follow a healthy lifestyle and apply it in their life activities.